Evaluating the Accuracy of Results for Teacher Implemented Trial-Based Functional Analyses. (September 2015) - Rispoli, Mandy; Ninci, Jennifer; Burke, Mack D.; Zaini, Samar; Hatton, Heather; Sanchez, Lisa
Trial-based functional analysis (TBFA) allows for the systematic and experimental assessment of challenging behavior in applied settings. The purposes of this study were to evaluate a professional development package focused on training three Head Start teachers to conduct TBFAs with fidelity during ongoing classroom routines. To assess the accuracy of the TBFA results, the effects of a function-based intervention derived from the TBFA were compared with the effects of a non-function-based intervention. Data were collected on child challenging behavior and appropriate communication. An A-B-A-C-D design was utilized in which A represented baseline, and B and C consisted of either function-based or non-function-based interventions counterbalanced across participants, and D represented teacher implementation of the most effective intervention. Results showed that the function-based intervention produced greater decreases in challenging behavior and greater increases in appropriate communication than the non-function-based intervention for all three children.